SOSIALISASI PERAWATAN KULIT UNTUK MENCEGAH JERAWAT: PENDEKATAN EDUKASI DI SMA PGRI Purwodadi - Wahyu Purwanjani; Maulita Saraswati; Iman Cahyani; Indriani Dini (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2022)
Background: Acne is a common skin problem that is often experienced by teenagers, which can be influenced by various internal and external factors. A good understanding of proper skin care is very important to prevent and treat acne. Purpose: Increase public understanding of the importance of skin care to prevent acne. Method: interactive counseling that includes information on the causes of acne and skin care steps. Results: There was an increase in participants' understanding after the activity, with positive feedback regarding the material. Conclusion: This activity is effective in increasing adolescent awareness about skin care to prevent acne.